2019
DOI: 10.1038/s41467-019-13417-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrating electric field modeling and neuroimaging to explain inter-individual variability of tACS effects

Abstract: Transcranial electrical stimulation (tES) of the brain can have variable effects, plausibly driven by individual differences in neuroanatomy and resulting differences of the electric fields inside the brain. Here, we integrated individual simulations of electric fields during tES with source localization to predict variability of transcranial alternating current stimulation (tACS) aftereffects on α-oscillations. In two experiments, participants received 20-min of either α-tACS (1 mA) or sham stimulation. Magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
192
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(225 citation statements)
references
References 69 publications
18
192
2
Order By: Relevance
“…We compared differences in error rates between congruent and incongruent trials for the different stimulation conditions whilst controlling for dose dependent effects of tACS (‘tACS-dose’) ( Evans et al, 2020 ; Kasten et al, 2019 ). tACS-dose was estimated by taking BOLD contrast between stimulation and sham conditions extracted from right aPFC ( Evans et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…We compared differences in error rates between congruent and incongruent trials for the different stimulation conditions whilst controlling for dose dependent effects of tACS (‘tACS-dose’) ( Evans et al, 2020 ; Kasten et al, 2019 ). tACS-dose was estimated by taking BOLD contrast between stimulation and sham conditions extracted from right aPFC ( Evans et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…3E). Although adapting tACS protocols to individual participants has been suggested as a crucial step to increase effect sizes and advance the field (25)(26)(27), neural parameters that can predict these individual differences remain elusive. Here, we report an analysis of combined data from 18 participants who participated in both our experiments.…”
Section: Experiments 1 Vs 2: Phase Of Speech-entrained Eeg Predicts Tamentioning
confidence: 99%
“…For example, there is typically no consistent tACS phase which leads to highest perceptual accuracy for all participants (7)(8)(9)(10). Individualizing brain stimulation protocols has therefore been proposed as a crucial step to advance the theoretical and practical application of this line of research (25)(26)(27). A recent study (59) reported that the phase relation between tACS and visual flicker modulates the magnitude of EEG responses to the flicker when tACS is turned off.…”
Section: Predicting Tacs Outcomes From Eeg Dataimplications For Futurmentioning
confidence: 99%
“…However, individualized tACS parameters might be more effective. Future studies might therefore consider the participant's individual anatomy as well as the individual peak frequency of the targeted neural oscillations [12,20]. In addition, increasing tACS intensity, duration, and/or perform repeated stimulation sessions might increase its neural efficacy.…”
Section: Discussionmentioning
confidence: 99%